2020
DOI: 10.1042/bsr20200858
|View full text |Cite
|
Sign up to set email alerts
|

Optimal blood pressure for the minimum all-cause mortality in Chinese ESRD patients on maintenance hemodialysis

Abstract: Blood pressure (BP) is a known prognostic marker for mortality in patients on maintenance hemodialysis (MHD). However, definition of the BP and its optimal values varied essentially among different MHD populations. Our purpose was to clarify these important clinical parameters in a Chinese MHD cohort. Accordingly, we reviewed the available records of patients on regular MHD during the past ten years and made a comparison between the deceased (n=81) and survival ones (n=131). Multiple logistic regression and Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(39 reference statements)
3
12
0
Order By: Relevance
“…This increase in BP which can be due to fluid overload, over activity of renin angiotensin system, erythropoietin administration and enhanced stimulation of the sympathetic nervous system. Our results are similar to the findings of Wang et al, 13 who reported a mean SBP of 143.2 ± 32.7mmHg and mean DBP of 79.0 ± 15.9 mmHg among hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…This increase in BP which can be due to fluid overload, over activity of renin angiotensin system, erythropoietin administration and enhanced stimulation of the sympathetic nervous system. Our results are similar to the findings of Wang et al, 13 who reported a mean SBP of 143.2 ± 32.7mmHg and mean DBP of 79.0 ± 15.9 mmHg among hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…15 Thus, the levels of MDA production can be used as a biomarker to estimate the level of OS. 16 When OS occurs, it triggers oxidation and subsequent damage to biological macromolecules, causing severe tissue damage. 17 Oxidative degradation of lipids yields MDA.…”
Section: P R O V I S I O N a L L Ymentioning
confidence: 99%
“…Cardio-cerebrovascular mortality is the main component of all-cause mortality in MHD patients, followed by infectious diseases and malignancies [30] . In this study, the 3-year cardio-cerebrovascular mortality rates between the two groups was not P r e p r i n t significant.…”
Section: Discussionmentioning
confidence: 99%